The importance of road infrastructural investment on rural economic growth in uganda - Moriba christine sebit (UCU, 2024)
ABSTRACT This study investigates the impact of road infrastructure investment on rural economic growth in Uganda, using Mukono District as a case study. The introduction highlights the significance of road infrastructure for socio-economic development in rural areas, where access to markets, services, and employment opportunities is limited. The research aims to assess the current state of road infrastructure, analyse its economic effects, and evaluate the challenges and opportunities associated with road development in Mukono District. The body of the research utilized a qualitative methodology, employing semi-structured interviews, focus group discussions, and participant observations. Data was collected from local government officials, community leaders, business owners, and residents to capture in- depth insights into how road infrastructure affects agricultural productivity, market access, and overall economic well-being. Findings indicated that while road investments have positively impacted agricultural productivity and market access, challenges such as poor maintenance, funding constraints, and governance inefficiencies continue to limit their full potential. In conclusion, the study identifies key areas for improvement, such as increased funding, better governance, and the involvement of public-private partnerships to enhance the effectiveness of road infrastructure investments. Recommendations include focusing on sustainable road development practices and community involvement to maximize the socio- economic benefits for rural communities in Mukono District.